A Reconfigurable Active Huygens' Metalens. Issue 17 (24th February 2017) - Chen, Ke; Feng, Yijun; Monticone, Francesco; Zhao, Junming; Zhu, Bo; Jiang, Tian; Zhang, Lei; Kim, Yongjune; Ding, Xumin; Zhang, Shuang; Alù, Andrea; Qiu, Cheng‐Wei
Abstract : Metasurfaces enable a new paradigm to control electromagnetic waves by manipulating subwavelength artificial structures within just a fraction of wavelength. Despite the rapid growth, simultaneously achieving low‐dimensionality, high transmission efficiency, real‐time continuous reconfigurability, and a wide variety of reprogrammable functions is still very challenging, forcing researchers to realize just one or few of the aforementioned features in one design. This study reports a subwavelength reconfigurable Huygens' metasurface realized by loading it with controllable active elements. The proposed design provides a unified solution to the aforementioned challenges of real‐time local reconfigurability of efficient Huygens' metasurfaces. As one exemplary demonstration, a reconfigurable metalens at the microwave frequencies is experimentally realized, which, to the best of the knowledge, demonstrates for the first time that multiple and complex focal spots can be controlled simultaneously at distinct spatial positions and reprogrammable in any desired fashion, with fast response time and high efficiency. The presented active Huygens' metalens may offer unprecedented potentials for real‐time, fast, and sophisticated electromagnetic wave manipulation such as dynamic holography, focusing, beam shaping/steering, imaging, and active emission control. Abstract : By loading controllable active elements, a subwavelength metasurface is proposed with real‐time local reconfigurability. A reconfigurable active Huygens' metalens is experimentally realized at microwave frequencies, which demonstrates for the first time that multiple and complex focal spots can be controlled simultaneously at distinct spatial positions and reprogrammable in any desired fashion, with a fast response time of 10 µs and high efficiency.